2015
DOI: 10.1111/cei.12664
|View full text |Cite
|
Sign up to set email alerts
|

Study of microRNAs (miRNAs) that are predicted to target the autoantigens Ro/SSA and La/SSB in primary Sjögren's Syndrome

Abstract: 1 These authors contributed equally to the study. SummaryThe elevated tissue expression of Ro/SSA and La/SSB autoantigens appears to be crucial for the generation and perpetuation of autoimmune humoral responses against these autoantigens in Sj€ ogren's syndrome (SS). The mechanisms that govern their expression are not known. miRNAs, the posttranscriptional regulators of gene expression, might be implicated. We have identified previously the miRNAs let7b, miR16, miR181a, miR200b-3p, miR200b-5p, miR223 and miR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 40 publications
2
34
0
3
Order By: Relevance
“…The Ro/SSA and La/SSB intracellular ribonucleoproteins are the major targets of autoimmune humoral responses in SS (18). A literature review found that there were ~30 miRNAs, including miR-181a, miR-16, target Ro/SSA (Ro52/E3 ubiquitin-protein ligase TRIM21 or Ro60/60 kDa SS-A/Ro ribonucleoprotein) and La/SSB mRNAs (19).…”
Section: Methodsmentioning
confidence: 99%
“…The Ro/SSA and La/SSB intracellular ribonucleoproteins are the major targets of autoimmune humoral responses in SS (18). A literature review found that there were ~30 miRNAs, including miR-181a, miR-16, target Ro/SSA (Ro52/E3 ubiquitin-protein ligase TRIM21 or Ro60/60 kDa SS-A/Ro ribonucleoprotein) and La/SSB mRNAs (19).…”
Section: Methodsmentioning
confidence: 99%
“…Significantly lower levels of miR200b‐5p, a miRNA which regulates expression of autoantibodies directed to intracellular autoantigens, La/SSB, were characterized in SS patients with MALT lymphoma compared with those without ( p < 0.05; Gourzi, Kapsogeorgou, Kyriakidis, & Tzioufas, ). Similarly, in the study of Kapsogeorgou, Papageorgiou, Protogerou, Voulgarelis, and Tzioufas (), miR200b‐5p was significantly downregulated in patients with SS who would develop or had NHL, and was able to discriminate this subset ( p < 0.0001) from those without lymphoma or those with non‐SS sialadenitis.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly lower levels of miR200b-5p, a miRNA which regulates expression of autoantibodies directed to intracellular autoantigens, La/ SSB, were characterized in SS patients with MALT lymphoma compared with those without (p < 0.05; Gourzi, Kapsogeorgou, Kyriakidis, & Tzioufas, 2015). Similarly, in the study of Kapsogeorgou, Papageorgiou, Protogerou, Voulgarelis, and Tzioufas (2018) Barone et al (2008) reported that CXCL12 was principally detected in infiltrated ducts and malignant B cells in the salivary glands of patients with SS.…”
Section: Geneticsmentioning
confidence: 94%
“…Some studies reported the overexpression of miR-146a and miR-155 in the PBMC of patients with primary SS. [24][25][26] Gourzi et al 27 identified miRNAs suspected to target Ro/SSA and La/SSB mRNAs in primary SS as follows: let-7b, miR-16, miR-181a, miR-200b-3p, miR-200b-5p, miR-223, and miR-483-5p. The overexpression of miR-16 in minor salivary glands (MSGs), miR-200b-3p in salivary gland epithelial cells (SGECs), and miR-223 collectively with miR-483-5p in PBMCs of SS patients compared to those in the sicca complaining controls has been reported.…”
Section: Discussionmentioning
confidence: 99%